2019
DOI: 10.5458/jag.jag.jag-2018_0012
|View full text |Cite
|
Sign up to set email alerts
|

A Novel α-Glucosidase of the Glycoside Hydrolase Family 31 from <i>Aspergillus sojae</i>

Abstract: We characterized an α-glucosidase belonging to the glycoside hydrolase family 31 from Aspergillus sojae. The α-glucosidase gene was cloned using the whole genome sequence of A. sojae, and the recombinant enzyme was expressed in Aspergillus nidulans. The enzyme was purified using affinity chromatography. The enzyme showed an optimum pH of 5.5 and was stable between pH 6.0 and 10.0. The optimum temperature was approximately 55 °C. The enzyme was stable up to 50 °C, but lost its activity at 70 °C. The enzyme acte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…In comparison, GH31 (containing α-glucosidases) present in three screened representative microorganisms (Blautia, Lactococcus and Enterococcus) suggested that starch and cellulose metabolism is more active in microorganisms associated with the low smoking population. 83 This observation is also verified by COG and KEGG. Among the 26 screened COGs, those associated with transcription, antibiotic resistance, and nucleic acid metabolism were predominantly linked to a high smoking rate, while the differentially represented KOs associated with a low smoking rate were primarily involved in carbohydrate, amino acid, and energy metabolism.…”
Section: Association Of Microbial Functions and Metabolisms To Smokingsupporting
confidence: 56%
“…In comparison, GH31 (containing α-glucosidases) present in three screened representative microorganisms (Blautia, Lactococcus and Enterococcus) suggested that starch and cellulose metabolism is more active in microorganisms associated with the low smoking population. 83 This observation is also verified by COG and KEGG. Among the 26 screened COGs, those associated with transcription, antibiotic resistance, and nucleic acid metabolism were predominantly linked to a high smoking rate, while the differentially represented KOs associated with a low smoking rate were primarily involved in carbohydrate, amino acid, and energy metabolism.…”
Section: Association Of Microbial Functions and Metabolisms To Smokingsupporting
confidence: 56%
“…The results of these assays were compared with those previously reported for AgdA. 19) The activities of AgdB and AgdA were determined based on the relative amounts of glucose released from their substrates. No trehalose-hydrolyzing activity was detected.…”
Section: Resultsmentioning
confidence: 99%
“…a Kinetic parameter of A. niger AgdA cited from a previous report. 19) b Weighted average molecular weight of soluble starch was 8,778 determined by gel permeation chromatography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations